Early Absenteeism and Academic Outcomes: Evidence from a Longitudinal Study - Goldie, Peter D.; Hogan, Frances C.; Gandhi, Jill; O'Connor, Erin E. (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
Socioeconomically Marginalized Youth of Color (SMYoC) across global contexts tend to receive lower academic grades and standardized test scores due to systemic racism and classism. Research suggests that preschool enrollment is associated with short-term positive academic effects, yet little is known about how absenteeism relates to later academic outcomes particularly among SMYoC. This is a crucial area of study as preschool can help to close opportunity gaps and promote educational equity, yet absenteeism may buffer its benefits. The present study investigated long-term associations between preschool absenteeism and academic outcomes and whether later absenteeism mediates this association among SMYoC in New York City. Analyses revealed significant negative associations between preschool absenteeism and both math and English language arts achievement in third through sixth grades. Additionally, we found mediation effects of assessment grade absenteeism (i.e., absenteeism rate during the year of the assessment) in third and sixth-grade math. Results highlight the importance of identifying strategies to increase preschool attendance rates to support academic outcomes.